Role of social capital in empowering rural women through income-generating activities in Sylhet District, Bangladesh - Akter, Aysha (2021)
Social capital has been recognized as an essential towards empowering rural women in the Sylhet District of Bangladesh. It facilitates their engagement in various Income Generating Activities (IGAs) as means of empowerment. IGAs have therefore, become an essential empowerment tool among rural women in the Sylhet District of Bangladesh because it gives them expanded access to resources and enhanced capabilities for self- reliance at both individual and collective levels. Majority of women have very little chance to take part in intra-household activities, socio-economic activities and have limited inter-linkage with people due to social, cultural and religious restrictions. This thesis examined the role played by social capital and participation towards the empowerment of women through IGAs in Bangladesh with specific focus on rural women in Sylhet District, Bangladesh. Therefore, this study aims to: (i) to describe the demographic characteristics of rural women participating in different IGAs in Sylhet District of Bangladesh, (ii) to measure the dimensions of social capital, participation and levels of empowerment in IGAs among rural women in the District under study (iii) to examine the relationship between social capital, participation and women empowerment in the study area, (iv) to examine the impacts of social capital (bonding, bridging and linking) on psychological and financial assets among rural women in the study area, (v) to explore the effect of socio-demographic factors on women empowerment through IGAs in the study area, and (vi) to examine the present socio- economic challenges hindering women empowerment through IGAs in Sylhet District of Bangladesh. This study is mainly a quantitative research, however, qualitative data were collected via a semi-structured interview for support and validation purpose. The study was conducted in two phases: quantitative survey which was followed by a qualitative interview. The study used questionnaire as its main instrument of quantitative data collection from a total of 328 randomly selected respondents. In the qualitative phase, the in-depth interview method was used for data collection and a total of twelve (12) informants were purposively selected and interviewed. The Pearson correlation analysis was measured to explain the relationships between participation, social capital and women empowerment. A multiple linear regression analysis was also deployed to identify the highest contributing factors of social capital towards women empowerment by using SPSS version-22 software and the qualitative thematic analysis were done by Nvivo software. Three proxies of social capital (bonding, bridging and linking) were measured in this study. The results show that more than 50% of the women had high levels of bonding. Bonding social capital was found to be the most contributing factor to women empowerment. The descriptive analysis of bridging social capital reveals that only 4.6% of the women were in the lower level of bridging social capital, with 40.4% being in the higher level of bridging and 55% in the moderate level. 63.2% of the women were in the lower level of linking, 30% had a moderate level and 6.8% had a high level of linking social capital. Participation in IGAs (subjective and objective) and bridging were also found to be significant in enhancing the women empowerment based on the results of the study. With regards to the psychological and financial dimensions of empowerment, the results indicate that level of bonding determines financial assets among rural women in the study area while the three dimensions of social capital (bonding, bridging and linking) altogether determines psychological assets among the rural women in South Surma Upazila of Sylhet district in Bangladesh. The data analysis showed that there is a significant relationship between participation, social capital and women empowerment in the Sylhet District of Bangladesh. The analysis equally indicated that among the socio- demographic factors, women’s level of education, marital status, personal income, credit received, training received and participation in IGAs determines their levels of empowerment. Taken together the findings of this study suggested that bonding, bridging, and linking are directly related to empowerment of women who are participating in different IGAs. The overall results indicated that the conceptualizations of bonding, bridging, linking and participation have provided a good understanding of empowerment among women as most of the findings appear to suggest. Since the level of bridging and linking among rural women ranged from medium to low levels, community development policy makers might focus on building and facilitating bridging and linking as dimensions of social capital in order to facilitate the empowerment of women in Bangladesh.